ЖИЙЕНБАЙ ИЗБАСҚАНОВ ЛИРИКАСЫНДА ГҮЗГИ ПЕЙЗАЖДЫӉ СҮЎРЕТЛЕНИЎ ӨЗГЕШЕЛИКЛЕРИ - Досымбетова, А. (FAN va JAMIYAT, 2023)
The article explores the peculiarities of landscape lyrics by Zh.Izbaskanov. His skill is analyzed in depicting natural landscapes. The uniqueness of the lyrical protagonist’s spiritual apologies is studied through the natural phenomena of autumn. Traditional and modern artistic research will be presented in the use of autumn landscapes. A number of poet’s works are analyzed related to autumn nature.